Functional Circuitry Effect of Ventral Tegmental Area Deep Brain Stimulation: Imaging and Neurochemical Evidence of Mesocortical and Mesolimbic Pathway Modulation - Settell, Megan L.; Testini, Paola; Cho, Shinho; Lee, Jannifer H.; Blaha, Charles D.; Jo, Hang J.; Lee, Kendall H.; Min, Hoon-Ki (Frontiers in Neuroscience, 2017)
Background: The ventral tegmental area (VTA), containing mesolimbic and mesocortical dopaminergic neurons, is implicated in processes involving reward, addiction, reinforcement, and learning, which are associated with a variety of neuropsychiatric disorders. Electrical stimulation of the VTA or the medial forebrain bundle and its projection target the nucleus accumbens (NAc) is reported to improve depressive symptoms in patients affected by severe, treatment-resistant major depressive disorder (MDD) and depressive-like symptoms in animal models of depression. Here we sought to determine the neuromodulatory effects of VTA deep brain stimulation (DBS) in a normal large animal model (swine) by combining neurochemical measurements with functional magnetic resonance imaging (fMRI). Methods: Animals (n=8 swine) were implanted with a unilateral DBS electrode targeting the VTA. During stimulation (130Hz frequency, 0.25ms pulse width, and 3V amplitude), fMRI was performed. Following fMRI, fast-scan cyclic voltammetry in combination with carbon fiber microelectrodes was performed to quantify VTA-DBS-evoked dopamine release in the ipsilateral NAc. In a subset of swine, the blood oxygen level-dependent (BOLD) percent change evoked by stimulation was performed at increasing voltages (1V, 2V, and 3V). Results: A significant increase in VTA-DBS-evoked BOLD signal was found in the following regions: the ipsilateral dorsolateral prefrontal cortex, anterior and posterior cingulate, insula, premotor cortex, primary somatosensory cortex and striatum. A decrease in the BOLD signal was also observed in the contralateral parahippocampal cortex, dorsolateral and anterior prefrontal cortex, insula, inferior temporal gyrus, and primary somatosensory cortex (Bonferroni-corrected < 0.001). During neurochemical measurements, stimulation time-locked changes in dopamine release were recorded in the NAc, confirming that mesolimbic dopaminergic neurons were stimulated by DBS. In the parametric study, BOLD signal changes were positively correlated with stimulation amplitude. Conclusions: In this study, the modulation of the neural circuitry associated with VTA-DBS was characterized in a large animal. Our findings suggest that VTA-DBS could affect the activity of neural systems and brain regions implicated in reward, mood regulation, and in the pathophysiology of MDD. In addition, we showed that a combination of fMRI and electrochemically-based neurochemical detection platform is an effective investigative tool for elucidating the circuitry involved in VTA-DBS.